The Application of Memetic Algorithm for Induction Motor Parameter Estimation - ทิพจร วิวัฒน์; ไกลถิ่น ชนะชน; เฉลิมกิจ จักรพงศ์ (Naresuan University Engineering Journal, 2018)
This paper presents the estimation of the steady state equivalent circuit parameters of induction motor by memetic algorithm with shuffle frog-leaping technic for local search. Parameter estimation of the motors is calculated by the optimization technique using maximum torque, full load torque and starting torque data. The results of the proposed method are compared with genetic algorithm and shuffle frog-leaping algorithm. The results reveal that the parameter estimation of the motor using memetic algorithm has the mean percentage error 6.7 % compared with the parameters from the test in laboratory.